Functional Status and Adaptation: Measuring Activities of Daily Living and Device Use in the National Health and Aging Trends Study. (August 2018) - Frochen, Stephen; Mehdizadeh, Shahla
Objective: The objective of this study is to evaluate the functional status and adaptation of older Americans and discover the factors that contribute to device use.Method: Using the community participants' portion of the first round of National Health and Aging Trends Study (NHATS), we demonstrate the prevalence of device use and reduction in activities, creating a multilevel measure of activities of daily living (ADL) functionality as compared with Katz's dichotomous measure. In determining whether adaptation is universal irrespective of age, sex, race, living arrangement, and income, or dependent on these variables, we create a measure of device use, performing a path analysis of the device use measure and sociodemographic variables, with disability score as an intervening measure.Results: ADL functionality becomes more nuanced between the Katz-ADL and NHATS-ADL. Age, sex, and living arrangement were predictors of device use; income was indirectly, whereas race was not.Discussion: When assessors design service plans, consideration should be given to older adults' ability, capacity, and resources to adapt.